PENDAMPINGAN WIRAUSAHA MANDIRI BAGI IBU RUMAH TANGGA DI DESA PUJORAHAYU KECAMATAN BELITANG - Garaika Garaika (Jurnal PkM Pemberdayaan Masyarakat, 2020)
Based on central statistical data the number of individual business operators in East OKU Regency has increased very rapidly. In Community Service activities carried out for three months using the In Class training method, On the Job training, apprenticeship, the results of activities that can be taken are business groups that receive assistance to understand about simple financial processing to distinguish between personal or family needs and needs business so that between income and expenditure is recorded in a simple business accounting book. Assistance of housewives who have a business is able to hone skills in innovating the latest products. The use of social media has a wide reach in marketing so that it automatically adds customers which will affect sales turnover.